The Impact of ASN Transformation on Human Resource Development in West Papua - Lande, Natan Tanduk; Rifdan, Rifdan; Nur, Andi Cudai (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
The transformation of State Civil Apparatus (Indonesia: Aparatur Sipil Negara /ASN) in West Papua represents a crucial policy initiative aimed at improving public service efficiency, yet its specific impact on human resource development in the region remains underexplored, particularly given West Papua's unique socio-cultural and geographical challenges. This research examines how ASN transformation influences human resource development in West Papua, focusing on implementation processes and outcomes. Using a qualitative approach, the study collected data through semi-structured interviews with purposively selected ASN personnel and government officials, complemented by document analysis. The findings reveal significant progress in human resource development through the implementation of an integrated Strategic Plan (RENSTRA), comprehensive training programs, and modernized recruitment processes using computer-based testing (CAT). The establishment of performance assessment systems and career advancement opportunities has enhanced ASN effectiveness and transparency. However, challenges persist, including uneven civil servant distribution, incomplete merit-based placement, and limited budget utilization for competency development programs. The research demonstrates that successful ASN transformation requires a balanced approach between technological advancement and human capital development, while considering the region's distinct geographical and social landscape. Evaluation results indicate that while substantial groundwork has been laid for improving public service delivery, continued attention to implementation challenges and local context remains essential for future success.